Біоскло та його застосування в сучасному лікуванні остеоонкологічних захворювань - Туранська, С. П.; Кусяк, А. П.; Петрановська, А. Л.; Туров, В. В.; Горбик, П. П.; Дубок, В. А.; Бур'янов, О. А.; Чорний, В. С.; Соболевський, Ю. Л.; Чехун, В. Ф. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2021)
Bone tumor diseases are one of the main problems in modern clinical practice. After surgery, some of the tumor cells capable of proliferation may remain, leading to tumor recurrence. In addition, surgical ablation of bone tumors creates bone tissue defects. Therefore, the problem of manufacturing specific biomaterials with a dual function of treating bone tumors and regeneration of bone defects has become a priority. The use of methods of targeted delivery and local controlled release of drugs contributes to the creation of the desired therapeutic concentration of drugs in the disease focus and increases their bioavailability. In recent years, promising samples capable of effective controlled release have been developed in which cisplatin, doxorubicin and gemcitabine have been used as model chemotherapeutic drugs. These approaches have been promising and have shown the potential to destroy residual tumor cells, however, they may become resistant to such drugs, which leads to treatment failure. The main purpose of the review is to summarize the latest world experience in the synthesis, research and use of composites based on bioactive ceramic materials and modern antitumor drugs as promising implants, embodying a new generation of complex remedies for targeted delivery with osteoconductive and antitumor properties, prolonged action, for local application. Examples are given of bioglass application with cytotoxic / cytostatic components, as well as results of development of the newest directions of antitumor therapy of bones, in which acquisition of resistance of tumor cells is not observed. The antitumor functions of such multifunctional samples are performed, for example, by chemotherapy, photothermal therapy, magnetic hyperthermia, and photodynamic therapy. These data are of scientific, practical and methodical interest.